0344 24-hour Ambulatory Blood Pressure and Insomnia: Exploring the Transition from Acute Insomnia to Recovery, Persistent Poor Sleep, or Chronic Insomnia. (27th April 2018) - Boyle, J T; Vargas, I; Muench, A; Gencarelli, A; Khader, W; Ellis, J; Perlis, M L
Abstract: Introduction: Chronic insomnia (CI) is highly prevalent and associated with significant medical morbidity, including hypertension. To date, no studies have been undertaken to assess this association over time where the subjects' clinical status was free to vary from the initial assessment to follow-up. The present investigation assessed ambulatory blood pressure (BP) over the course of 24 hours on two separate occasions in four subject groups. Methods: Twenty adults (mean age = 58.8) were recruited from a national study on the natural history of insomnia. This sub-sample participated in two lab studies (initial visit and 3-month follow-up). Subjects were categorized into four groups (5 per group): Good Sleepers who remained good sleepers (GS); subjects with AI who recovered (REC); Persistent Poor Sleep (PPS); or CI. Ambulatory BP was assessed serially (q30 min) for 24 hours. Results: At Time 1, all subjects, on average, had an 11% reduction in systolic BP during the nocturnal period (pre-sleep-onset to nocturnal nadir). Results from a one-way ANOVA showed a significant group difference in mean 24-hour systolic and diastolic BP (systolic, F = 54.8, p < .001; diastolic, F = 12.8, p < .001) such that the CI group had lower mean 24-hr BP as compared to the other three groups (mean 24-hr systolic/diastolic BP in mmHg [SD]: GS = 120.2 [13.1]/72.6 [11.7], REC = 121.4 [13.1]/74.6 [12.3], AI = 115.1 [17.9]/78.3 [13.7], CI = 105.5 [13.7]/72.0 [11.1]). Conclusion: These data suggest that individuals with new onset CI do not exhibit elevated blood pressure and do not appear to show an absence of "dipping". It remains possible, if not likely, that the deleterious "effects" of insomnia on blood pressure require substantially longer periods of illness to accrue. Support (If Any): Perlis: NIH R01AG041783 & Ellis: Economic and Social Research Council (RES-061-25-0120-A).